Elevated alpha-synuclein caused by SNCA gene triplication impairs neuronal differentiation and maturation in Parkinson's patient-derived induced pluripotent stem cells - Oliveira, L. M. A. (2015)
We have assessed the impact of α-synuclein overexpression on the differentiation potential and phenotypic signatures of two neural-committed induced pluripotent stem cell lines derived from a Parkinson´s disease patient with a triplication of the human SNCA genomic locus. In parallel, comparative studies were performed on two control lines derived from healthy individuals and lines generated from the patient iPS-derived neuroprogenitor lines infected with a lentivirus incorporating a small hairpin RNA to knock down the SNCA mRNA. The SNCA triplication lines exhibited a reduced capacity to differentiate into dopaminergic or GABAergic neurons and decreased neurite outgrowth and lower neuronal activity compared with control cultures. This delayed maturation phenotype was confirmed by gene expression profiling, which revealed a significant reduction in mRNA for genes implicated in neuronal differentiation such as delta-like homolog 1 (DLK1), gamma-aminobutyric acid type B receptor subunit 2 (GABABR2), nuclear receptor related 1 protein (NURR1), G-protein-regulated inward-rectifier potassium channel 2 (GIRK-2) and tyrosine hydroxylase (TH). The differentiated patient cells also demonstrated increased autophagic flux when stressed with chloroquine. We conclude that a two-fold overexpression of α-synuclein caused by a triplication of the SNCA gene is sufficient to impair the differentiation of neuronal progenitor cells, a finding with implications for adult neurogenesis and Parkinson´s disease progression, particularly in the context of bioenergetic dysfunction.